2002
DOI: 10.1002/chir.10104
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate receptor ligands: Synthesis, stereochemistry, and enantiopharmacology of methylated 2‐aminoadipic acid analogs

Abstract: Homologation and substitution on the carbon backbone of (S)-glutamic acid [(S)-Glu, 1], as well as absolute stereochemistry, are structural parameters of key importance for the pharmacological profile of (S)-Glu receptor ligands. We describe a series of methyl-substituted 2-aminoadipic acid (AA) analogs, and the synthesis, stereochemistry, and enantiopharmacology of 3-methyl-AA (4a-d), 4-methyl-AA (5a-d), 5-methyl-AA (6a-d), and (E)-Delta(4)-5-methyl-AA (7a and 7b) are reported. The compounds were resolved usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…In fact the L-enantiomeric form exerts an agonist activity, while the D-enantiomeric form acts as an antagonist (Brauner-Osborne et al, 2000;Guldbrandt et al, 2002). Since NMDA has been implicated in both cell death and neuronal excitotoxicity in AD (Butterfield and Pocernich, 2003), clearer delineation of the relative abundance of the D-and L-enantiomers of α-aminoadipic acid, would be useful to allow better interpretation of how these might modulate neurotoxicity via NMDA receptors with respect to AD pathology.…”
Section: Discussionmentioning
confidence: 99%
“…In fact the L-enantiomeric form exerts an agonist activity, while the D-enantiomeric form acts as an antagonist (Brauner-Osborne et al, 2000;Guldbrandt et al, 2002). Since NMDA has been implicated in both cell death and neuronal excitotoxicity in AD (Butterfield and Pocernich, 2003), clearer delineation of the relative abundance of the D-and L-enantiomers of α-aminoadipic acid, would be useful to allow better interpretation of how these might modulate neurotoxicity via NMDA receptors with respect to AD pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-amino adipidic acid ( α -AAA) decreased from baseline to day 1 following ketamine treatment, while in placebo it increased to 230 min and then slightly declined ( p = 0.006). A decrease in circulating levels of α -AAA would be beneficial, as it is a known mGluR2 agonist (Guldbrandt et al 2002), which has been reported to be an astrocytic toxin that can induce depressive-like behavior (Domin et al 2014). However, as the circulating levels were near the limit of quantitation, these findings need to be replicated.…”
Section: Treatment Effectsmentioning
confidence: 99%
“…[b] Data from ref. 22 Three out of the four tested compounds bound to NMDA receptor, with (R)-8 having the best affinity (Ki = 14 μM). Interestingly, the Ki value of (R)-8 is almost identical to that of (R)-AA, our reference NMDA antagonist.…”
mentioning
confidence: 94%